Do Foreign Aid Transfers Distort Incentives and Hurt Growth? Theory and Evidence from 75 Aid-recipient Countries - George Economides; Sarantis Kalyvitis; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper, foreign aid transfers can distort individual incentives, and hence hurt growth, by encouraging rent-seeking as opposed to productive activities. We construct a model of a small growing open economy that distinguishes two effects from foreign transfers: (i) a direct positive effect, as higher transfers allow the financing of infrastructure; (ii) an indirect negative effect, as higher transfers induce rent-seeking competition on the part of self-interested individuals. In this framework, the growth impact of aid is examined jointly with the determination of rent-seeking behavior. We test the main predictions of the model for a cross-section of 75 aid-recipient countries between 1975 and 1995. There is evidence that aid has a direct positive effect on growth, which is however significantly mitigated by the adverse indirect effects of associated rent-seeking activities. This is especially the case in recipient countries with relatively large public sectors.
Keywords: 330; foreign aid; incentives; growth